Association of visceral adiposity and its longitudinal increase with the risk of diabetes in Chinese adults: A prospective cohort study. Issue 7 (31st August 2018) - Xia, Ming‐Feng; Lin, Huan‐Dong; Chen, Ling‐Yan; Wu, Li; Ma, Hui; Li, Qian; Aleteng, Qiqige; Chen, Ying; Sun, Yi‐Xuan; Hu, Yu; Pan, Bai‐shen; Li, Xiao‐Ying; et al.
Abstract: Objective: A Chinese visceral adiposity index (CVAI) was recently established to estimate the visceral fat area in Chinese adults. This study aimed to investigate the risk of incident prediabetes and diabetes in relation to visceral adiposity calculated by CVAI. Methods: A total of 2558 subjects with normal plasma glucose levels from the Shanghai Changfeng Study were enrolled in a prospective cohort study. The independent associations of basal visceral fat area by CVAI and its longitudinal change with incident prediabetes and diabetes were identified using Cox regression analyses. Results: During an average of 4.4 years of follow‐up, 546 (21.3%) and 99 (3.9%) of 2558 nondiabetic subjects developed prediabetes and diabetes, respectively. Visceral fat area by CVAI and its longitudinal increase were independently associated with incident prediabetes and diabetes in Chinese adults. In a multivariable‐adjusted regression model, CVAI, as well as its annual change, was the strongest independent predictor of incident prediabetes (HR, 1.383 [1.162‐1.647]) and diabetes (HR, 1.607 [1.092‐2.364]) compared with other estimates of obesity (BMI and waist circumference). Receiver operating characteristic curve analyses showed that CVAI had better performance than BMI and waist circumference for the prediction of prediabetes and diabetes in Chinese adults. Conclusions: Visceral adiposity plays a pivotal role in the pathogenesis of diabetes, and the visceral adiposity estimated by CVAI is superior to the traditional estimates of obesity for the prediction of incident prediabetes and diabetes in Chinese adults.